Overconsumption dalam Influencer Culture di Media Sosial: Kajian Tafsir al-Azhar Karya Buya Hamka - Naila Royani; Abdul Rahman; Mustapa Mustapa (YASIN, 2026)
Although studies on tabdzir in Tafsir Al-Azhar have received attention in several previous studies, discussions that specifically link it to the phenomenon of overconsumption in influencer culture on social media remain limited. This study aims to evaluate and describe overconsumption behavior through the contextualization of the concept of tabdzir in Q.S. Al-Isra’ verses 26–27 according to Tafsir Al-Azhar by Buya Hamka. This study used a qualitative approach with a library research design. The data sources consisted of primary and secondary data collected through literature study, documentation, digital database searches, and review of scientific journals. Data were analyzed using a content analysis approach, while data validity was strengthened through source triangulation and theory triangulation. The results showed that in Tafsir Al-Azhar, tabdzir is rooted in the disorientation of wealth utilization to fulfill pseudo-inner satisfaction, not merely in the nominal amount of material wealth. These findings indicate that overconsumption in influencer culture represents a dual crisis of spirituality that has the potential to trigger ingratitude for blessings, neglect of the rights of the poor, and ecological damage. The conclusion of this study affirms that the ethical values of the Qur’an have contextual relevance as a moral compass as well as an instrument of solution-oriented criticism in navigating the complexity of today’s digital economic disruption. The implications of this study provide theoretical contributions to the development of contextual tafsir studies and Islamic consumption ethics, as well as open opportunities for further research on strategies to prevent the negative impacts of excessive consumption in digital spaces.